Transactional Communication and Teacher Retention in Selected Private Secondary Schools in Kyotera District, Uganda - Gobera Paul; Mark Kiiza (Journal of Current Research and Studies, 2024)
The study aimed to investigate the impact of head teachers' sharing of vision and objectives with teachers, their collaboration in managing the school, and their use of effective communication channels like notifications, alerts. School transaction communication has a significant influence on teacher retention in selected private secondary schools in Uganda. The study sampled 186 research participants and used a descriptive case research design to enable in-depth understanding of the variables under investigation. The findings revealed that teachers in Kyotera district follow the school calendar, adhere to school guidelines, and are aware of the school's objectives. The study concludes that, head teachers need to demonstrated practicality, cooperation, negotiation, and collaboration in order to forester teachers’ retention in private schools in Uganda. The study also concludes there should regular school information, having maintained effective communication channels, sent message alerts, communicated passionately and integrity, and responded to office calls in emergencies. The study recommended that head teachers in Kyotera district continue using transactional leadership in managing secondary schools, as it has proven effective in retaining teachers in private secondary schools in Kyotera, Uganda.